A vinculação das receitas tributárias e as contribuições no sistema tributário nacional - Castellani, Fernando Ferreira (2006)
The scope of the present paper is the study of constitutional and legal precepts related to the taxing kind called special contributions, particularly regarding the destination of taxation. The study of a taxing kind presupposes the definition of distinguishing criteria and of the applicable legal system. As normally expected, these criteria are established by the Constitution, via introduction of a rule of taxing competence. Special contributions demand classification based on its specific destination. Such classification will influence, in a decisive way, the allowable destination to be given to the funds collected by taxation. Destination of public revenues must be described and contained in the budgetary rule of the tax entity, imposing to the own tax entity the utilization of the resources. This association, for its structural and specific character of special contribution, must not be disregarded or changed, under pain of implying in the legal possibility of repetition of the amounts paid by the debtor